ANALISIS KOLABORASI DIVISI BUSINESS DEVELOPMENT DAN DIVISI HUMAN RESOURCES DALAM MENGIMPLEMENTASIKAN STRATEGI PENGEMBANGAN BISNIS DAN SDM PADA PERUSAHAAN CV COKRO BERSATU (BLUDER COKRO) - Putri, Ardhelia Anggita; Anggraini, Nesmaya; Wahyuningsih, Dwi Warni (Jurnal Pijar, 2025)
This study aims to analyze the collaboration between the Business Development Division and the Human Resources Division in implementing business development and human resource development strategies at CV Cokro Bersatu (Bluder Cokro). The research approach uses a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The results show that collaboration between the two divisions is effective through strategic planning based on product innovation, distribution expansion, and strengthening the quality of human resources through training, HRIS, and KPI determination. The implementation of Planning, Organizing, Actuating, Controlling (POAC) management is proven to support operational efficiency and product quality control. Meanwhile, the evolution of marketing strategies from Marketing 1.0 to 6.0 allows the company to adapt to changes in consumer behavior through the use of digital media and application technology. In the distribution aspect, planning optimization and cost efficiency have succeeded in increasing the profit percentage from 2% to 23%. Improved employee performance contributes significantly to the success of business expansion and increased company competitiveness. This study emphasizes the importance of synergy between divisions and the integration of business-HR strategies to drive sustainable growth in food manufacturing companies in the digital era.